Effects of α-ZrP on Crystallinity and Flame-Retardant Behaviors of PA6/MCA Composites - Yuanfang Xiao; Jiayou Xu; Siwen Huang; Haiming Deng (International Journal of Polymer Science)
Novel flame-retardant Polyamide6/Melamine cyanurate-alpha-zirconium phosphate (PA6/MCA-α-ZrP) composites were prepared via the incorporation of the modified MCA (MCA-α-ZrP) into PA6. MCA-α-ZrP were synthesized through the self-assembly of α-ZrP, Melamine (ME), and cyanuric acid (CA) molecules. The results of differential scanning calorimetry (DSC) and X-ray diffraction (XRD) showed that the incorporation of enough α-ZrP (30 wt% MCA) caused the increased crystallinity of PA6 and tended to form γ phase. The thermogravimetric analysis (TGA) and heat distortion temperature (HDT) test illustrated that the α-ZrP could increase the residue and HDT values of PA6/MCA and showed a synergistic effect with MCA. The combination of MCA and α-ZrP caused the enhancement of vertical burning test (UL-94) rating. Cone calorimeter test (CCT) gave clear evidences that PA6/MCA-10α-ZrP composites with low heat release rate (HRR), low total heat release (THR), and high amounts of char residues after combustion compared with PA6/MCA and PA6/MCA-30α-ZrP. What is more, excellent mechanical properties were kept even though MCA and α-ZrP were dispersed not as good as expected.